Homeopathic medications in modern medicine - Ilyukevich, M. K. (Запорізький державний медико-фармацевтичний університет, 2025)
Aim – to study the effectiveness of the homeopathic method in the treatment and prevention of various diseases.
Keywords: тези доповідей